2018
DOI: 10.1038/s41419-018-0310-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification to induce CXCR2 overexpression in mesenchymal stem cells enhances treatment benefits in radiation-induced oral mucositis

Abstract: Radiation-induced oral mucositis affects patient quality of life and reduces tolerance to cancer therapy. Unfortunately, traditional treatments are insufficient for the treatment of mucositis and might elicit severe side effects. Due to their immunomodulatory and anti-inflammatory properties, the transplantation of mesenchymal stem cells (MSCs) is a potential therapeutic strategy for mucositis. However, systemically infused MSCs rarely reach inflamed sites, impacting their clinical efficacy. Previous studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…Certainly, the cellular migration activity influences the number of homing MSCs. Moreover, the migration activity is strongly associated with chemokines and their receptors such as chemokine C‐X‐C motif chemokine 12 and CXCR2 (Chang et al, ; Shen et al, ). Whether HO‐1 overexpression influences the migration activity of MSCs by modulating the expression and/or function of chemokines and their receptor remains to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the cellular migration activity influences the number of homing MSCs. Moreover, the migration activity is strongly associated with chemokines and their receptors such as chemokine C‐X‐C motif chemokine 12 and CXCR2 (Chang et al, ; Shen et al, ). Whether HO‐1 overexpression influences the migration activity of MSCs by modulating the expression and/or function of chemokines and their receptor remains to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CCL2 expression by cancer-associated fibroblasts has been shown to support the growth of breast cancer stem cells (92), while CXCR4 was shown to be enriched in a subset of glioma cancer stem cells (93). Furthermore, CXCR2 is expressed in MSC and CXCR2 overexpressing MSCs can be used to accelerate mucosa wound healing (94). Both CXCR5 and CXCR4 are involved in metastasis of PCSLC prostate cancer stem-like cells (95), and inhibition of CXCR4 alters the homing of quiescent stem-like prostate cancer cells to bone (96).…”
Section: Chemokines Regulate Tumor Aggressiveness and Metastasismentioning
confidence: 99%
“…While the etiology and the pathogenic mechanisms of OM have not been fully elucidated yet, several studies have reported a major role of DNA damage and reactive oxygen species (ROS) during the early phases of oral and intestinal mucositis [ 4 7 ]. Thus, either limiting ROS generation or increasing their detoxification during CT/RT stands as a rational and promising strategy to prevent OM onset and/or reduce its severity [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%